Pengaruh Pelatihan Kerja Terhadap Produktivitas Kerja Karyawan Di PT Pal Indonesia (Persero) Divisi Kapal Perang - Yusuf Rohmad Mustofa; Nur Aini Anisa; Nur Farida (Populer: Jurnal Penelitian Mahasiswa, 2023)
Mustofa Yusuf Rohmad 961201026, The effect of job training on employee work productivity at PT PAL Indonesia (Persero). Warship Division High School of Youth Economics Advisor Anisa Nur Aini, S.PD,. M.PD The purpose of this study was to determine the effect of training and work discipline on employee work productivity at PT PAL Indonesia (Persero) warship division. The type of research used in this research is quantitative research with a descriptive approach. The sampling technique used is a saturated sample. The population that is the focus of the research is 122 employees who have worked permanently in the Warship Division of PT. PAL Indonesia (Persero). Observation data collection techniques, questionnaires. The results of this study indicate that work training (X1) partially has a positive and significant effect on work productivity.